An investigation on the effect of ultra-precision machined patterns in wetting transition. (15th September 2011) - Cheng, C.T.; To, S.; Chan, C.Y.; Cheung, C.F.
This paper aims to study the influence of micro patterns on the wetting transition of a hydrophilic material. Surfaces with a designed pattern with various groove widths are machined by ultra-precision raster milling. The impact of different groove widths of the machined patterns on wetting transition will be discussed by studying the spreading of droplets on respective patterns. Contact angle and elongation length were measured using a contact angle goniometer. The present work revealed that machined surfaces on a hydrophilic material with micro patterns can achieve composite solid-liquid-air interfaces when the scales of the machined pattern fall into a critical range. The results from the experiments can provide useful information for designing self-cleaning surfaces.